Los nuevos programas y políticas en materia de investigación de la Facultad de Derecho de la Universidad de Buenos Aires y su fundamento jurídico y democrático - Alegre, Marcelo (2011)
This paper is intended to describe and explain the new programs and academic policies implemented by the University of Buenos Aires Law School during 2010-2011 to promote research activities among its faculty and graduate and undergraduate students. A brief examination on the execution of the different programs is also included, as well as a short explanation on their legal and ethical background.